Pharmacological correction efficiency of endothelial dysfunction in treatment of children with asthma - V. M. Dudnyk; K. V. Khromykh (Kazimierz Wielki University, 2015)
Dudnyk V. M., Khromykh K. V. Ефективность фармакологічної корекції ендотеліальної дисфункції в лікуванні дітей, хворих на бронхіальну астму = Pharmacological correction efficiency of endothelial dysfunction in treatment of children with asthma. Journal of Education, Health and Sport. 2015;5(3):199-206. ISSN 2391-8306. DOI: 10.5281/zenodo.16362 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%283%29%3A199-206 https://pbn.nauka.gov.pl/works/549883 http://dx.doi.org/10.5281/zenodo.16362 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011 - 2014 http://journal.rsw.edu.pl/index.php/JHS/issue/archive   Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 20.01.2014. Revised 27.02   УДК 616.248 - 053:611.018.74:616 - 008.6   ЕФЕКТИВНОСТЬ ФАРМАКОЛОГІЧНОЇ КОРЕКЦІЇ ЕНДОТЕЛІАЛЬНОЇ ДИСФУНКЦІЇ В ЛІКУВАННІ ДІТЕЙ, ХВОРИХ НА БРОНХІАЛЬНУ АСТМУ   PHARMACOLOGICAL CORRECTION EFFICIENCY OF ENDOTHELIAL DYSFUNCTION IN TREATMENT OF CHILDREN WITH ASTHMA   В. М. Дудник, К. В. Хромих V.M. Dudnyk, K.V. Khromykh   Вінницький національний медичний університет ім. М.І. Пирогова Vinnitsa National Medical University   Article Background. In recent years all over the world, including Ukraine, there is a tendency to increase the incidence of asthma children shift its start at an earlier age and heavier flow. Despite numerous studies on the pathogenesis of asthma has recently received considerable attention is the role of endothelial dysfunction in the mechanisms of control and capabilities of this disease. The aim of our study was to evaluate the effectiveness of pharmacological correction of endothelial dysfunction in children with allergic asthma. Materials and methods. We have examined 224 child with allergic asthma in acute disease aged 6 to 17 years (mean age 9,42 ± 3,43 years who were divided into two groups, representative by age, sex, severity and duration of disease, and duration and dose of ongoing basic anti-inflammatory therapy. In the study group (n = 45) was conducted correction of endothelial dysfunction "Tivortin aspartate" (orally, 5 ml (1 g) 3 times a day during meals, for 30 days). All children contents were determined in serum homocysteine and VEGF, and performed ultrasonography of the carotid and brachial arteries. Results and discussion. Control of asthma improved in the intervention group patients, resulting in a decrease in the number of children who have night and day symptoms, limited physical activity and the need for b2-agonists on short-acting (17.32 - 55.65)%, than in children with comparison group. After 4 weeks of treatment tivortinom homocysteine and VEGF in the study group patients was lower at 26.48% and 36.03%, respectively, than in children with asthma with the comparison group. Intima-media thickness carotid artery in the group of children who received a combination of IGC with tivortin decreased to 0,83 ± 0,02 mm, which is 14.43% lower than in patients who received standard therapy of asthma base. As regards the ultrasound brachial artery, they also decreased in the range (12.39 - 19.56) %, reflecting the success of the treatment. Conclusion.  Сhildren with asthma need for pharmacological correction of endothelial dysfunction, allowing  to have better control of this disease. Key words: bronchial asthma, children, endothelial dysfunction, treatment.   Реферат Актуальність проблеми. За останні роки в усьому світі, в тому числі й Україні, спостерігається тенденція до зростання захворюваності на бронхіальну астму (БА) дітей, зміщення її початку на більш ранній вік та важчий перебіг. Не зважаючи на чисельні дослідження щодо патогенезу БА, останнім часом приділяється значна увага ролі ендотеліальної дисфункції в механізмах розвитку та можливостях контролю даного захворювання. Метою нашого дослідження було оцінити ефективність  фармакологічної корекції ендотеліальної дисфункції у дітей, хворих на алергічну бронхіальну астму. Матеріали та методи. Нами було обстежено 224 дитини із алергічною БА у періоді загострення захворювання віком від 6 до 17 років (середній вік 9,42 ± 3,43 років, які були поділені на дві групи, репрезентативні за віком, статтю, важкістю та тривалістю захворювання, а також тривалістю та дозами проведеної базисної протизапальної терапії. В основній групі (n = 45) проводилась корекція ендотеліальної дисфункції «Тівортін аспартатом» (перорально, по 5 мл (1 г) 3 рази на добу під час прийому їжі, протягом 30 днів). Усім дітям визначались вміст в сироватці крові гомоцистеїну та VEGF, а також проводилась ультрасонографія сонної та плечової артерії. Результати та їх обговорення. Контроль над перебігом БА покращився в основній групі пацієнтів, що проявлялось зменшенням кількості дітей, які мали нічні та денні симптоми, обмежену фізичну активність та необхідність застосування b2-агоністів короткої дії на (17,32 - 55,65) %, ніж у дітей із групи порівняння. Після 4-тижневого курсу лікування тівортіном вміст гомоцистеїну та VEGF в основній групі пацієнтів був меншим на 26,48 % та 36,03 % відповідно, ніж  у дітей, хворих на БА із групи порівняння.